Postfire changes in forest carbon storage over a 300‐year chronosequence of Pinus contorta‐dominated forests. Issue 1 (1st April 2013) - Kashian, Daniel M.; Romme, William H.; Tinker, Daniel B.; Turner, Monica G.; Ryan, Michael G.
Abstract : A warming climate may increase the frequency and severity of stand‐replacing wildfires, reducing carbon (C) storage in forest ecosystems. Understanding the variability of postfire C cycling on heterogeneous landscapes is critical for predicting changes in C storage with more frequent disturbance. We measured C pools and fluxes for 77 lodgepole pine ( Pinus contorta Dougl. ex Loud var. latifolia Engelm.) stands in and around Yellowstone National Park (YNP) along a 300‐year chronosequence to examine how quickly forest C pools recover after a stand‐replacing fire, their variability through time across a complex landscape, and the role of stand structure in this variability. Carbon accumulation after fire was rapid relative to the historical mean fire interval of 150–300 years, recovering nearly 80% of prefire C in 50 years and 90% within 100 years. Net ecosystem carbon balance (NECB) declined monotonically, from 160 g C·m −2 ·yr −1 at age 12 to 5 g C·m −2 ·yr −1 at age 250, but was never negative after disturbance. Decomposition and accumulation of dead wood contributed little to NECB relative to live biomass in this system. Aboveground net primary productivity was correlated with leaf area for all stands, and the decline in aboveground net primary productivity with forest age was related to a decline in both leaf area and growth efficiency. Forest structure was an important driver of ecosystem C, with ecosystem C, live biomass C, and organic soil C varying with basal area or tree density in addition to forest age. Rather than identifying a single chronosequence, we found high variability in many components of ecosystem C stocks through time; a >50% random subsample of the sampled stands was necessary to reliably estimate the nonlinear equation coefficients for ecosystem C. At the spatial scale of YNP, this variability suggests that landscape C develops via many pathways over decades and centuries, with prior stand structure, regeneration, and within‐stand disturbance all important. With fire rotation projected to be <30 years by mid century in response to a changing climate, forests in YNP will store substantially less C (at least 4.8 kg C/m 2 or 30% less).